Empirical understanding of and perceived ability in statistical concepts: a Rasch measurement approach - Abu Kassim , Noor Lide; Ismail, Nor Zatul-Iffa; Mahmud, Zamalia; Zainol, Mohammad Said (2010)
This study investigates students’ conceptual knowledge and understanding of basic statistical concepts and compares it against statistical competence, which is associated with discrete statistical knowledge and basic interpretive skills. It also examines the correspondence between students’ perceived ability and their empirical understanding of the concepts. Two instruments were developed: a 20-item test to measure students’ empirical understanding of the basic statistical concepts and a questionnaire with matching items to measure their perceived ability of these concepts. For a direct comparison of the two, students’ responses to the test and questionnaire items were jointly analyzed using Rasch analysis. Results of the analyses conducted indicate that conceptual understanding of basic statistical concepts is more difficult to attain that statistical competence. The results also suggest that students more often than not overestimated their understanding of basic statistical concepts, particular those requiring conceptual understanding of the concepts.